2018
DOI: 10.5337/2018.207
|View full text |Cite
|
Sign up to set email alerts
|

Business model scenarios and suitability: smallholder solar pump-based irrigation in Ethiopia. Agricultural Water Management – Making a Business Case for Smallholders

Abstract: Research ReportsThe publications in this series cover a wide range of subjects-from computer modeling to experience with water user associations-and vary in content from directly applicable research to more basic studies, on which applied work ultimately depends. Some research reports are narrowly focused, analytical and detailed empirical studies; others are wide-ranging and synthetic overviews of generic problems.Although most of the reports are published by IWMI staff and their collaborators, we welcome con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Worqlul, Collick, Rossiter, Langan, and Steenhuis () showed that in the Gilgel Abay basin less than 0.1% of the potential irrigable land could be irrigated with the available surface water resources. The greatest weakness in these studies is whether sufficient surface or groundwater is available for planned irrigation (Otoo, Lefore, Schmitter, Barron, & Gebregziabher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Worqlul, Collick, Rossiter, Langan, and Steenhuis () showed that in the Gilgel Abay basin less than 0.1% of the potential irrigable land could be irrigated with the available surface water resources. The greatest weakness in these studies is whether sufficient surface or groundwater is available for planned irrigation (Otoo, Lefore, Schmitter, Barron, & Gebregziabher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Giordano et al (2012) estimated that investments in motorized pumps could benefit some 185 million farmers and generate net revenues of around USD 22 billion 9 . Otoo et al (2018) estimate the potential area that could be irrigated by solar photovoltaic (PV) pumps in Ethiopia to be between 1.1 and 6.8 Mha, depending on assumptions about depth to groundwater. Small motorized pumps, and more specifically solar pumps, have the additional potential benefit of being useful for multiple purposes, by women as well as men (Burney et al 2013;Nigussie et al 2017).…”
Section: The Potential For Expanding Small-scale Irrigation In Sub-samentioning
confidence: 99%
“…Farmers more often rely on informal lenders, especially relatives and friends or their own resources, as found in Ghana by Namara et al (2014). Community-based semi-formal lenders are growing in importance in many countries, but often do not offer medium-term loans that would support the purchasing of equipment such as pumps (Otoo et al 2018;Ayele 2015). Financial service providers face high costs and risks in lending to a dispersed population of smallholders; but providing credit for irrigated agriculture has the advantage of reducing risk and seasonality compared to rainfed farming, and pumps may be offered as collateral for the loan.…”
Section: Financial Services For Small-scale Irrigation In Sub-saharanmentioning
confidence: 99%
See 2 more Smart Citations